Metodologia para análise da confiabilidade no planejamento de sistemas de distribuição utilizando matrizes lógicoestruturais - Marques, Leandro Dutra (2016)
With the constant requirement for improving the levels of quality and reliability in the power distribution systems, especially with regard to the quality of service (duration and frequency of outages), it has intensified the need for a better planning and operation of the electrical grids in all voltage levels. One of the main challenges in the distribution systems is the balance between customer satisfaction, regulation (legislation) of power sector and the return on the capital invested by the utilities. Often this search for resource optimization ends up being hampered by process problems, lack of tools, few experts, among other issues, in most cases favoring a poor planning of electrical system reliability. In many cases the planning criteria used by the distribution companies are related only to the equipment load, voltage level control and new customer access, so it seldom has the reliability among the elements. Even when reliability is part of these criteria it's usually based just on the assessment of historical outages. Due to this deficiency, the subject of this dissertation is the use of a method for forecasting reliability in the electrical planning stage, i.e., it will be proposed actions such as installation of new switches, use of different network topologies, reduction of failure rates and recovery times, and finally calculated the impact of these actions on the reliability KPIs. The methodology for forecasting the indicators is based on logical-structural matrix, which use information such as failure rates and mean time to restore the power to different network segments. It will also be presented a case study proposing planning actions in a real distribution grid with subsequent evaluation of the impact on reliability KPIs of an electrical utility.